FROM SHARING TO STREAMING: TECHNOLOGY, LEGISLATION AND AGENCY IN THE DIGITAL PHONOGRAPHIC INDUSTRY FROM 1996 TO THIS DAY - Saa, Guido Agustin (AoIR Selected Papers of Internet Research, 2026)
This paper aims to compare, from the perspective of political economy of communication and philosophy of technology, two distinct historical periods of music consumption via the Internet (from 1996 to 2007 and from 2007 to today) considering the technological, social, aesthetic and authorial changes that have occurred over the last thirty-three years. This broad period begins with the Telecommunications Act of 1996, a true legal milestone that marks the beginning of a considerable deregulation of the Internet. Since this deregulation, which freed the Internet from legal surveillance regarding rights such as Copyright, the entire planet (but, of course, firstly Europe and USA) began to access an ever-increasing volume of audio files, thanks to an innovative format that managed to reproduce audio with acceptable fidelity without being excessively heavy in terms of storage. This “miraculous” format, the mp3, designed to be enjoyed in noisy contexts, with relaxed and distracted listening, while running other programs on the computer or traveling from one place to another (Sterne, 2006) not only enabled new forms of listening but also new ways of socializing and sharing (Bull, 2005). In the era of the “digital condition” (Sadin, 2013), that is, the era in which most of citizens’ interactions began to be framed and mediated by the use of the Internet, listening to audio files was inseparable from the idea of sharing them, without necessarily requiring financial compensation (that would be the difference between “sharing” and “piracy”).